The Teacher-Made Multiple-Choice Tests Quality for Natural Science Subject - Putra, Erik Nanda; Syamsurizal, Syamsurizal; Lufri, Lufri; Zulyusri, Zulyusri (LPPM Undiksha, 2021)
The questions used as evaluations test the memory aspects of the cognitive, affective, and psychomotor domains in Bloom's taxonomy which are not optimal. Some science teachers still have difficulty formulating questions, so the instruments developed by teachers are not valid. The research objective is to analyze the quality quantitatively (reliability, discriminatory power, difficulty level, and distractor effectiveness). This study aims to This research is a descriptive study. The population in this study were all student answer sheets on the Science Assessment Exam. The sampling technique used was total sampling with a sample of 107 student answer sheets. Data analysis using ANATES ver. 4.0.2 programs. The results based on the research obtained: 1) reliability of 0.50 with criteria; 2) the distinguishing power of good and bad categories that dominates is 30% while 25% as moderate and 7.5% is very good; 3) the level of difficulty obtained with moderate criteria is 62.5%, easy questions are 15%, difficult questions are 12.5% , and challenging questions are 2.5%; 4) the effectiveness of distractors, there are 35 items or 87.5% of effectiveness distractors that work well. As for the five items, the quality of the distractors does not work, or their effectiveness is terrible. Thus, it can be said that the questions met the criteria well, but some need to be revised.